Japayuki - Gorospe, Rizzi Eugenio; Cantor, Olivia L. (2012)
"This undergraduate thesis explores the OFW film genre and the phenomenon of diaspora. The Filipino family culture is also depicted in the film. Family is always at the core and ultimately, each member just wants the best for everyone. It also questions and condemns, with humor, some Filipino traits, like the quick judgment on foreigners/balikbayans, and also the unfortunate connotation of the term "Japayuki"".
Vita.
Undergraduate thesis (A.B. Film and Audio Visual Communication)--University of the Philippines, Diliman.
Keywords: Japayuki (Short film).; Short films -- Philippines; Comedy films -- Philippines